Interaction in Virtual Learning Environments (VLEs) - an Ethical Perspective - Rasmussen, Anne (Proceedings of the International Conference on Networked Learning, 2006)
This paper attempts to contribute to a deeper insight into the ways in which we are challenged in communicative and collaborative situations in virtual learning environments (VLEs). In particular the focus is on communication in asynchronous environments, more specific discussion boards. By introducing the concepts of surveillance, trust, risk and spontaneity, it is explained how the precondition for being able to establish learning processes fundamentally depends on the degree to which we are in a position to create space for trustful collaboration. It is argued that collaboration build on trustful relations is communication enacted through engaged commitment, where strategic deliberations has been put aside. It is exemplified how this might be obtained or suppressed in VLEs, partly through a discussion of virtual presence but also by questioning the traditional use and role of metaphors in design.